TINGKATKAN KEMAMPUAN BERBAHASA MELALUI MULTILANGUAGE BERBASIS ETNOLANGUAGE DI SDN SUMBERSARI 2 - Saadah, Lailatus; Taqiyuddin, Ahmad; Mahendri, Wisnu; Rizqiyah, Alfiyatur; Kusumo, Ahmad Wasis Joyo; Qomariyah, Siti Nur (Universitas Islam Malang, 2024)
Many students are poor in language aspects, including regional languages, Indonesian, English and Arabic, and there are no multilingual books that attract students' interest, and due to differences in curriculum, there are differences in lessons in each class. Students' language skills are felt to be less than optimal. Therefore, language introduction and training is held. The aim of this activity is to improve students' language skills. The approach method that can be used are socialization, education, implementation, and evaluation by combining Jigsaw and Outdoor Study learning methods. The stages that have been implemented in the Multilingual Introduction and Training work program have an influence on students' work results. This plays an important role in motivating students to develop skills in mastering English and Arabic. The results of the training show data on increasing learning outcomes from 20 students who were held in a pre-test with an average score of 62, a maximum score of 78 and a minimum score of 50. After receiving multilingual training, the students were able to achieve a score that met the KKM, namely more than 79 by 60 %, so it can be concluded that multilingual training can be said to be quite effective.